2020
DOI: 10.1186/s12885-020-06828-y
|View full text |Cite
|
Sign up to set email alerts
|

Fertility sparing surgery vs radical surgery for epithelial ovarian cancer: a meta-analysis of overall survival and disease-free survival

Abstract: Background: The aim of this systematic review and meta-analysis was to compare overall survival and disease-free survival after fertility sparing surgery (FSS) vs radical surgery in stage 1 epithelial ovarian cancer (EOC). Methods: A systematic literature search of PubMed, BioMed Central, Scopus, CENTRAL (Cochrane Central Register of Controlled Trials) and Google scholar was carried out. Databases were searched for English language studies from inception to 1st November 2019. Adjusted hazard ratios (HR) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Large retrospective studies and metaanalyses have found that for stage I epithelial ovarian cancer, fertility-sparing surgery did not appear to compromise disease-free survival (DFS) or overall survival (OS) compared with radical surgery. [76][77][78][79][80][81][82][83][84][85] Although clear cell histology is associated with increased risk of poor outcomes, 83 some studies have shown that even among patients with stage I clear cell, fertility-sparing surgery does not increase risk of relapse or shorten survival compared with radical surgery. 77,78,81,82,85 Large retrospective studies among patients with stage I borderline ovarian tumors have found that recurrence rate and survival is similar for those treated with fertility sparing versus radical surgery.…”
Section: Fertility Sparing Options For Stage I Diseasementioning
confidence: 99%
“…Large retrospective studies and metaanalyses have found that for stage I epithelial ovarian cancer, fertility-sparing surgery did not appear to compromise disease-free survival (DFS) or overall survival (OS) compared with radical surgery. [76][77][78][79][80][81][82][83][84][85] Although clear cell histology is associated with increased risk of poor outcomes, 83 some studies have shown that even among patients with stage I clear cell, fertility-sparing surgery does not increase risk of relapse or shorten survival compared with radical surgery. 77,78,81,82,85 Large retrospective studies among patients with stage I borderline ovarian tumors have found that recurrence rate and survival is similar for those treated with fertility sparing versus radical surgery.…”
Section: Fertility Sparing Options For Stage I Diseasementioning
confidence: 99%
“…This conservative treatment is considered in AYAs with a strong desire to preserve fertility and with limited disease and no visible abnormalities during surgery. However, only observational, retrospective series comparing FSS and non-FSS in selected patients are available and controversy about women with high-risk prognostic factors remains [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radical surgery is unlikely to reduce the risk of recurrence of certain histological subtypes 32 . In a previous study, there was no signi cant difference in overall survival between stage I and radical surgery in EOC 33 . Prognosis may be more related to the natural history of the disease and the cancer type rather than to the speci c type of surgery 34 .…”
Section: Discussionmentioning
confidence: 75%